التحليل الجغرافي لواقع المرأة الإفريقية التعليمي والصحي: دراسة جغرافية - السيد محمد علي محمود محمود (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2021)
يعد وضع النساء في أي مجتمع مقياساً لمدى تطور ونمو هذا المجتمع. ولقد اهتمت المحافل الدولية بقضايا المرأة ومنها: التعليم والصحة.     ويتأثر واقع المرأة التعليمي والصحي بالعديد من العوامل منها: طبيعة الإطار الاجتماعي والثقافي المحيط بالمرأة، والتنمية الاقتصادية المتحققة في المجتمع، بالإضافة إلى سياسات الدولة المتعلقة بالمرأة.    وتهدف الدراسة الحالية إلى التعرف على الواقع التعليمي والصحي للمرأة الأفريقية خلال سنوات زمنية مختلفة، ومقارنة هذا الواقع بأوضاع المرأة على مستوى العالم وأقاليمه المختلفة، وإبراز التباين المکاني والأسباب الجغرافية لتباين الواقع التعليمي والصحي للمرأة الأفريقية عبر أقاليم ودول القارة.    وتضمنت الدراسة الواقع التعليمي والصحي للمرأة الأفريقية، وتناولت من خلاله تطور واقع المرأة التعليمي والصحي، والتباين المکاني للواقع التعليمي والصحي للمرأة الأفريقية عبر أقاليم ودول القارة.    وأظهرت الدراسة أنه رغم تحسن الواقع التعليمي والصحي للمرأة الأفريقية مع مرور الزمن، إلا أنه ما زال واقعها التعليمي والصحي أدنى من نظيره بالعديد من أقاليم العالم. کما أظهرت الدراسة وجود تباين وتفاوت بين أقاليم ودول القارة فيما يتعلق بالواقع التعليمي والصحي للمرأة.     وأوصت الدراسة بضرورة تعزيز تعليم الفتيات من خلال حملات توعية بأهمية تعليمها، وخفض التکاليف المباشرة وغير المباشرة لتعليم الفتيات، ومناهضة الزواج المبکر قبل السن القانوني، وتحسين البيئة المدرسية، والتوسع في إنشاء المدارس لتقليل الوقت والمسافة إلى المدرسة، کما أوصت الدراسة بضرورة الاهتمام ببرامج التثقيف الصحي للمرأة الأفريقية، والتوسع في خدمات تنظيم الأسرة، ووضع آليات مستدامة لتمويل علاج مرض نقص المناعة البشرية المکتسبة/ الإيدز، ومراعاة حصول المرأة على الرعاية الصحية خاصة خلال الفترة الإنجابية. The status of women in any society is a measure of the extent of development   and growth of this society. The forums focused on women's issues, including: education and health.                                                                                          The educational and health status of women is influenced by many factors, including: the nature of the social and cultural framework surrounding women, and the economic development achieved in society, in addition to the state's policies related to women.                                                                                     The current study aims to identify the educational and health status of African women during different years, and to compare this reality with the status of women at the level of the world and its different regions, and to highlight the spatial variation and geographical reasons for the variation in the educational and health status of women across the regions and countries of the continent.                        The study included the educational and health status of African women, and dealt with through it the development of the educational and health status of women, and the spatial variation of the educational and health status of African women across the regions and countries of the continent.                                     The study   showed that despite the    improvement of the educational and health status of the African woman with the passage of time, her educational and health status  is still less than that of many regions of the world. The study also showed the presence of different variation among the countries of the continent with regard to the educational and health status of women.                                           The study recommended the necessity of enhancing girls' education through awareness campaigns about the importance of their education, reducing direct and indirect costs for girls ’education, opposing early marriage before the legal age, improving the school environment, and expanding the construction of schools to reduce time and distance to reach them, and the study also recommended that attention must be paid to health education programs for African women and expanding family planning services, developing sustainable mechanisms to finance treatment for HIV/AIDS, and taking into account women's access to health care, especially during the reproductive period.